Effect of seed priming with salicylic acid on Antioxidant potential and enzyme inhibitory activity of moth beans (Vigna aconitifolia) - Makwana, Tanvi; Patel , Vinayak (Journal of Postharvest Technology, 2024)
Moth bean is an important legume and consumed widely in India. The present investigation deals with the study of effect of various concentrations of salicylic acid (SA) on phenolic composition and bioactivity of Moth bean. The germination was done by priming the moth beans in varying concentrations of SA (0 ppm / L, 50 ppm L, 100 ppm / L, 150 ppm / L and 200 ppm / L).The results showed that the total phenolics, flavonoid and proline levels were increased significantly (p ≤ 0.05) in the germinated samples compared to raw moth beans. The FRAP and DPPH-RSA also increased in germinated moth beans. The carbohydrate digestive enzymes (α-amylase and α-glucosidase) activity was inhibited significantly in germinated moth beans. The carbohydrate digestive enzymes (α-amylase and α-glucosidase) activity was inhibited significantly in germinated moth beans. The person correlation showed a significant relation between total phenolics and TAC. The results suggested that the seeds priming with SA have increased antioxidant potential and enzyme inhibitory effect to improve the health benefits through diet.